Cognitive Performance among Adult Male Smokers and Non-Smokers in Rural Chennai, India: A Community -Based Cross-Sectional Study - Manikandan, Venmathi; Mer, Hetal Tejas; Kadiyala, Prathyusha; Dutta, Ruma; Merli G (National Journal of Community Medicine, 2026)
Background: Smoking is associated with accelerated cognitive decline, warranting evaluation in underserved rural populations. Hence, with this aim the current study is taken up to compare cognitive function between smokers and non-smokers in a rural area. Methods: A community-based cross-sectional study was conducted among 302 adult participants from a rural area. Sociodemographic and smoking-related data were obtained through a pretested local-language questionnaire. Cognitive function was assessed using Montreal Cognitive Assessment (MoCA) tool. Data were analysed using Chi-square, correlation analysis, t test and multivariable linear regression in SPSS version 25. Results: Among the 302 participants, 44% were smokers and 56% were non-smokers. Smokers demonstrated significantly lower MoCA scores compared with non-smokers (24.53 ± 2.21 vs. 25.28 ± 2.18; p = 0.003) and cognitive impairment was more prevalent in the smoking group. A moderate inverse relationship was observed between smoking index and MoCA scores (r = -0.361; p <0.001). Among smokers, sleep disturbances, memory problems and concentration changes were associated with cognitive impairment. After adjustment, smoking was not significantly associated with cognitive performance, however age, education and occupation showed significant association. Conclusion: Public awareness must be strengthened regarding the cognitive consequences of smoking, alongside its recognised physical health effects.